Investigação da corrosão do aço carbono AISI 1020 em soluções de NaCl utilizando microscopia óptica in situ - Santos, Rapher Donizete Moreira (2016)
According to recent information from the World Corrosion Organization, annually, approximately 2.2 trillion of global GDP is spent on corrosion-related damage. These expenses are almost the GDP of the seventh world economy in 2015, India. Corrosion-related problems occur in different materials and in various industrial sectors such as automobile, shipbuilding, petrochemical, oil companies. One important source of corrosion in the industry is presence of chloride in aqueous solutions. This work presents a study of the corrosion of carbon steel AISI 1020 in aqueous NaCl solution from 0.1 and 0.25 mol/L at temperatures of 25° and 45° C. The steel corrosion was investigated using open circuit potential measurements (Eoc), and polarization curves (PC) coupled to optical microscopy in situ. Thus, the influence of these two factors was evaluated by the interpretation of the effects using a factorial design. From the images of the temporal series obtained by optical microscopy in situ carried during the polarization curves, it was possible to analyze the behavior and characteristics of the corrosion process, such as the average corrosion potential, corrosion rate, eroded fraction, and quantifying the maximum diameter of the pits. Through the obtained results, it is possible to observe the direct influence of concentration and temperature of the corrosion process in the carbon steel AISI 1020, with the increase in the amount of corroded pits and the eroded fraction. It is possible to observe that the corrosion process starts by individual pits, which is converted to mass propagated pits known as pit colony. The development of individual pits was relatively fast, with less than 200 seconds and a maximum diameter up to 600 μm containing area of around 2 x 10^5 μm^2.